Echocardiographic predictors for persistent functional mitral regurgitation after aortic valve replacement in patients with aortic valve stenosis - Matsumura, Yoshiki (2010)
Roberto M. Saraiva. Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta a informação no documento.